(untitled) (Journal of Health, Population and Nutrition, 2013)
Malaria remains a public-health concern in Nigeria despite huge global investments in the production and distribution of insecticide-treated bednets (ITNs) to protect people from Plasmodium falciparum parasite. Information on the use of ITNs is needed for designing strategies for its effective use. Focus group discussions (FGDs) were conducted in communities from 3 geopolitical zones of Nigeria. The people had poor knowledge of malaria and mosquito bites, which resulted in wrong perception and misuse of the nets as door and window blinds to protect entire household since only two nets were given per household. The use of community structures (traditional leaders/village heads, youths, churches, and mosques) was suggested to ensure effective distribution of nets, sensitize, and monitor net-use in the communities. Health education would dispel misconceptions that ITNs could kill, curtail human fertility, and that local gin (Kai-Kai) would induce sleep and make one oblivious of mosquito nuisance. J HEALTH POPUL NUTR 2013 Jun; 31(2): 243-251 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16389